2009
DOI: 10.1111/j.1468-0092.2009.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐collapse: The Re‐emergence of Polity in Iron Age Boğazköy, Central Anatolia

Abstract: Summary How communities reorganize after collapse is drawing increasing attention across a wide spectrum of disciplines. Iron Age Boğazköy provides an archaeological case study of urban and political regeneration after the widespread collapse of eastern Mediterranean Late Bronze Age empires in the early twelfth century BC. Recent work at Boğazköy has significantly expanded our understanding of long‐term occupation in north central Anatolia. This work counters previous suggestions that Boğazköy was abandoned af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…If we sample the full range of geochemical variability in the geology of the region, the local ceramic compositional range should be encompassed, allowing us to differentiate non-local from local ceramics. Previous work has demonstrated the general effectiveness of this strategy (Grave et al 2008;Kealhofer et al 2009).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…If we sample the full range of geochemical variability in the geology of the region, the local ceramic compositional range should be encompassed, allowing us to differentiate non-local from local ceramics. Previous work has demonstrated the general effectiveness of this strategy (Grave et al 2008;Kealhofer et al 2009).…”
Section: Methodsmentioning
confidence: 94%
“…These most commonly represent geological provenance, but can also reflect clay processing techniques (removal and/or addition of minerals; see Grave et al 2008). Statistical results were graphed and manipulated in three-dimensional space to evaluate group distribution (shape and density) in relation to local sediment samples (see Grave et al 2008;Kealhofer et al 2009 for a more detailed discussion of methods).…”
Section: Methodsmentioning
confidence: 99%
“…Previous analysis has shown that Chalcolithic ceramics were manufactured using local sediments 25. As there is no documentation of trade in handmade earthenware ceramics in Anatolia during this period, the compositional groups identified reflect the diversity in the local geography of each site (Tables 4–6).…”
Section: Pxrf Analysis Of Chalcolithic Ceramics From Turkeymentioning
confidence: 99%
“…Bronson (2006; see also Lewis 1975) usefully defines the way in which people use or discard aspects of the real or imagined past through stimulus or template regeneration. Kealhofer et al (2009) recently adopted a regeneration approach for the reemergence of complexity at Bogazkoy after the Hittite collapse. This approach places a different value on dark ages as periods of reorganization and activity rather than catastrophe and passivity.…”
Section: Dark Ages Resilience and Regenerationmentioning
confidence: 99%